Russian Geopolitical Interests in the Middle East in Post Arab Spring Period - Abida Rafique; Sadaf Farooq; Husnul Amin (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This article aims to assess the Russian geopolitical interests in the Middle East following the post Arab Spring period. The Arab Spring has reshaped Middle East’s geopolitics by engaging the leading world powers in the region’s developments, both directly and indirectly. In this regard, this study seeks to assess the geopolitical implications of "Arab Spring" turmoil in light of Russia’s involvement in influencing geopolitics of the region. Since the Arab Spring, Russia has possessed valuable assets for asserting its strategic aura in the region, the most important of which is its unwavering commitment to the preservation of national identities and state order in the Middle East. In-depth analysis of the conflict also underscores Russia’s influence in the Middle East as well as influence of its foreign policy in the region. United States already maintains a strong presence in the region, which may be viewed as having seemingly contradictory, given the interests of global powers. This study investigated how Russia created an equilibrium to maintain a strategic balance of power as well as the bandwagoning in the entire region.